2020
DOI: 10.3390/ijms21228476
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Tumor Cells, Neurons, and Microglia in the Glioma Microenvironment

Abstract: Despite significant strides made in understanding the pathophysiology of high-grade gliomas over the past two decades, most patients succumb to these neoplasias within two years of diagnosis. Furthermore, there are various co-morbidities associated with glioma and standard of care treatments. Emerging evidence suggests that aberrant glutamate secretion in the glioma microenvironment promotes tumor progression and contributes to the development of co-morbidities, such as cognitive defects, epilepsy, and widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 114 publications
(215 reference statements)
0
62
0
Order By: Relevance
“… 42–44 Therefore, when studying the potential acquisition of anti-tumoral properties by microglia, their crosstalk with other cell types, for example macrophages, astrocytes, and neurons, will have to be taken into account. 45 , 46 Hence, these investigations should grant interest for further investigation of the contribution of microglia to the initiation, progression, and response of DIPG tumors to treatments.…”
Section: Discussionmentioning
confidence: 99%
“… 42–44 Therefore, when studying the potential acquisition of anti-tumoral properties by microglia, their crosstalk with other cell types, for example macrophages, astrocytes, and neurons, will have to be taken into account. 45 , 46 Hence, these investigations should grant interest for further investigation of the contribution of microglia to the initiation, progression, and response of DIPG tumors to treatments.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides an overview of the existing evidence of reciprocal crosstalk between tumour cells and the brain parenchyma in meningiomas. Meningiomas express several factors, which are known to have chemotactic properties on microglia in glioblastoma multiforme (e.g., CCL2, CX3CL1, SDF-1, G-CSF and GM-CSF) [ 18 , 26 , 56 , 69 ]. We inferred that brain invasion in meningioma is mandatory to elicit an immune response in the brain parenchyma; however, direct invasion is only seen in a minor subset of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages and microglias showed mutual activation and counterbalance in glioma immune microenvironment and tumor progression. The specific and unique roles of microglia and macrophages depend on their localization in and around the tumor ( Radin and Tsirka, 2020 ). Studies on IDH mutated gliomas have found that macrophage transcription programs on microglias increase with tumor grade ( Venteicher et al, 2017 ).…”
Section: Immune Microenvironment In Gliomamentioning
confidence: 99%